KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU SEKOLAH DI SD NEGERI UJONG PATIHAH DAN SD NEGERI ALUE BATA - Nurul Istiwana; Nasir Usman; Murniati AR (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2021)
Principal leadership plays an important role in planning, developing, encouraging, supervising and evaluating schools so that a goal is achieved effectively, efficiently in improving the quality of schools. The purpose of the study was to determine the principal's leadership in the preparation, 1) quality improvement school principal's rules and regulations, 2) quality improvement principal program, 3) the principal's strategy for improving school quality and, 4) barriers to school principals in improving school quality at SD Negeri Alue Bata and SD Negeri Ujong Patihah, Nagan Raya Regency. This study uses a qualitative approach with a descriptive method. Data collection was obtained through interviews, observation and documentation. The subjects of the study were the principal, deputy principal, teacher, superintendent and head of school accreditation. The results of the study found that 1) the rules of discipline of the principal were prepared by the principal with the approval of educators and educational personnel who delivered during the meeting, 2) the principal's program in the form of an annual work program, a semester work program whose preparation is assisted by a teacher, an end-of-semester extracurricular program, 2) The principal's strategy is to hold teacher meetings and student guardian meetings, complete learning books, procurement of new buildings, selection of new students and transfer students. Cooperation with stakeholders in preparation for accreditation, discipline in school regulations, holding technology training for teachers, involving teachers in the KKG, providing equipment and materials in overcoming the corona disease outbreak. Strategic planning in the form of significant and time, 3) barriers to school principals applied, lack of teacher discipline in collecting learning tools, lack of interest in reading students in the library, some teachers did not join in preparing for accreditation due to lack of concern and sense of responsibility for school progress. Abstrak Kepemimpinan kepala sekolah berperan penting dalam menyusun perencanaan, mengembangkan, mendorong, mengawasi dan mengevaluasi sekolah sehingga tercapai suatu tujuan secara efektif, efisien dalam meningkatkan mutu sekolah. Tujuan penelitian adalah untuk mengetahui kepemimpinan kepala sekolah dalam penyusunan, 1) peraturan tata tertib kepala sekolah peningkatan mutu, 2) program kepala sekolah peningkatan mutu, 3) strategi kepala sekolah peningkatan mutu sekolah, dan 4) hambatan kepala sekolah peningkatan mutu sekolah di SD Negeri Alue Bata dan SD Negeri Ujong Patihah Kabupaten Nagan Raya. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Pengumpulan data di peroleh melalui wawancara, observasi dan dokumentasi. Subjek penelitian adalah kepala sekolah,wakil kepala sekolah,guru, pengawas dan kepala bidang pengakreditasian sekolah. Hasil penelitian di temukan, yaitu 1) peraturan tata tertib kepala sekolah disusun oleh kepala sekolah atas persetujuan pendidik dan tenaga kependidikan yang sampaikan saat rapat, 2) program kepala berupan program kerja tahunan, program kerja semester yang penyusunannya dibantu oleh guru, program ekstrakurikuler akhir semester, 3) Strategi kepala sekolah yang di terapkan mengadakan rapat guru dan rapat wali murid, melengkapi buku pembelajaran, pengadaan gedung baru, penyeleksian murid baru dan murid pindahan. Kerja sama dengan stakeholder dalam persiapan akreditasi, kedisplinan terhadap peraturan sekolah, mengadakan pelatihan tekhnologi untuk guru, mengikut sertakan guru mengikuti KKG, menyediakan peralatan dan bahan dalam mengatasi wabah penyakit corona. Perencanaan strategi berupa signifikan dan time, 4) hambatan kepala sekolah yang di terapkan kurangnya kedisipinan guru dalam mengumpulkan perangkat pebelajaran, kurang minat membaca siswa di perpustakaan, beberapa guru tidak ikut bergabung dalam mempersiapkan akreditasi karena kurangnya kepedulian dan rasa tanggung jawab terhadap kemajuan sekolah. Kata Kunci: Kepemimpinan, Kepala Sekolah, Mutu Sekolah